Exploring the mediating role of dimensions of academic task engagement in the relationship among student-teacher relationship, academic task value, and positive development outcomes - Getahun Tadesse Abren; Reda Darge Negasi; Amare Sahle Abebe (Cogent Psychology)
This study explored the mediating role of dimensions of academic task engagement in the relationship among student-teacher relationships, academic task value, and positive development outcomes. A correlational research design was used, and a cross-sectional survey was conducted with 500 students from grades 9 and 10 across five selected secondary schools. Researchers employed a multi-stage sampling technique to select participants. The study utilized structural equation modeling (SEM) to examine the mediation effect. The results of SEM revealed significant positive correlations among academic task value, student-teacher relationships, and engagement dimensions, explaining 88% of the variance in positive development outcomes. Significant direct effects were observed for student-teacher relationship (β = 0.292, 95% CI [0.139, 0.452], p < 0.001) and perceived academic task value (β = 0.185, 95% CI [0.071, 0.311], p = 0.004), with dimensions of academic task engagement mediating these relationships. The findings provide strong evidence that positive student–teacher relationship and a high perceived value of academic tasks significantly contribute to students’ positive development outcomes, with dimensions of academic task engagement (i.e. cognitive, behavioral, and affective) serving as crucial mediators. These results underscore the importance of fostering supportive educational environments to enhance students’ positive developmental outcomes. Educators should prioritize the cultivation of meaningful student-teacher relationship and the enhancement of academic task value within the curriculum, as these factors are essential for promoting student academic task engagement and positive development outcomes. Nonetheless, the cross-sectional design limits causal inference and the reliance on self-reports may introduce bias, suggesting the need for future longitudinal and mixed-methods research to validate and deepen understanding of these relationships over time.